Lassiter [videorecording (DVD)] - Selleck, Tom, 1945-; Seymour, Jane, 1951-; Hutton, Lauren; Hoskins, Bob (Hen's Tooth Video, 2010)
Nick Lassiter is a suave, debonair, man-about-town and thief. Whether he's charming high society at dinner or emptying their safes in the dead of night, Lassiter excels at what he does. On the eve of WWII Lassiter finds himself in London, where local authorities are well aware of his history as a notorious cat burglar. When word leaks out that a cache of uncut diamonds is to be smuggled through the German embassy, Lassiter is coerced by police and the FBI to perform one last heist on their behalf.